2020
DOI: 10.7759/cureus.10272
|View full text |Cite
|
Sign up to set email alerts
|

Not All Fun and Games: A Case Report of Contact Dermatitis Related to Slime and Play-Doh

Abstract: Slime and Play-Doh have been gaining popularity among adolescents and preteens. Both are gooey, viscoelastic substances that can be morphed and molded into virtually anything imaginable. Slime can be made from several household products including school glue and borax, which have both been linked to cases of irritant and allergic contact dermatitis, conditions that historically involve activation of many immune-regulatory cells such as Langerhans' cells and T cells. We review the rising incidence of contact de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…All reports are recent and included seven studies from 2018, five from 2019, and four from 2020 (Tables 1 and 2). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, seven are from the United States, whereas the remaining are from France, Belgium, Brazil, Switzerland, Turkey, Canada, Spain, and Tunisia, published during the period between 2000 and 2021. From the selected 16 studies, 5 reported more than one case of intoxication while the remaining studies reported only a single case.…”
Section: Resultsmentioning
confidence: 99%
“…All reports are recent and included seven studies from 2018, five from 2019, and four from 2020 (Tables 1 and 2). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, seven are from the United States, whereas the remaining are from France, Belgium, Brazil, Switzerland, Turkey, Canada, Spain, and Tunisia, published during the period between 2000 and 2021. From the selected 16 studies, 5 reported more than one case of intoxication while the remaining studies reported only a single case.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, for all the many wonderful educational aspects about making Borax Slime, there are significant consequential downsides to making it. There is a growing body of research that shows health consequences of making Borax Slime, including contact dermatitis and pediatric burns in children. For example, playing with slime was determined to be the cause of pruritic rash and skin discoloration of a healthy 4-year-old child . The symptoms lasted for several days after contact with the slime, and required a topical steroidal treatment to remedy .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research that shows health consequences of making Borax Slime, including contact dermatitis and pediatric burns in children. For example, playing with slime was determined to be the cause of pruritic rash and skin discoloration of a healthy 4-year-old child . The symptoms lasted for several days after contact with the slime, and required a topical steroidal treatment to remedy . In another more severe instance, a 10-year-old child exhibited blisters on the child’s hand and fingers that grew progressively worse during the course of several days after making Borax Slime .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations